Coding da Vinci – Das Playbook (De Gruyter, 2023)
Since 2014, the project "Coding da Vinci," which was funded by the German Federal Cultural Foundation from 2019 to 2022, has been connecting communities of cultural enthusiasts and technologically minded people with German art institutions to unfold the creative potential of our digital cultural heritage. This publication does not just report on the project but also provides a practical guide to successfully organizing a cultural data hackathon.